Botulinum Toxin A Facilitated Laparoscopic Repair of Complex Ventral Hernia - Tang, Fu-Xin; Ma, Ning; Huang, Enmin; Ma, Tao; Liu, Chuang-Xiong; Chen, Shuang; Zong, Zhen; Zhou, Tai-Cheng (Frontiers in Surgery, 2022)
Background: Complex ventral hernia repair can be challenging despite the recent advances in surgical techniques. Here, we aimed to examine the effectiveness of preoperative combined use of botulinum toxin A (BTA) and preoperative progressive pneumoperitoneum (PPP) for surgical preparation of patients with complex ventral hernia. Methods: In this prospective, observational study, we included 22 patients with complex ventral hernia between January 2018 and May 2021. All patients were treated with BTA injections into the lateral abdominal muscles and PPP before hernia repair. The lengths of abdominal wall muscles, the volumes of the incisional hernia (VIH), the volumes of the abdominal cavity (VAC), and the VIH/VAC ratio were measured before and after BTA and PPP using abdominal CT scan. All Hernias were repaired using laparoscopic intra-peritoneal onlay mesh (IPOM) or laparoscopic-open-laparoscopic (LOL) techniques. Results: Imaging showed a significant increase in the mean lateral abdominal muscle length from 13.1 to 17.2 cm/side (p < 0.01). Before and after BTA and PPP, the mean VIH was 894 cc and 1209 cc (P < 0.01), and the mean VAC was 6692 cc and 9183 cc (P < 0.01). The VAC increased by 2491 cc (P<0.01) and was greater than the mean VIH before PPP. An average reduction of 0.9% of the VIH/VAC ratio after BTA and PPP was obtained (p >0.05). All hernias were surgically reduced with mesh, hernia recurrence occurred in only two patients. Conclusions: The preoperative combined use of PPP and BTA increased the abdominal volume, lengthened the laterally retracted abdominal muscles, and facilitated laparoscopic closure of large complex ventral hernia.